# this equation

Options
Registered Posts: 157 Dedicated contributor 🦉
Hi any one here can show me the way to solve this equation please.
2(2x+1)-3(x-1)=8 I got answer to 3x+1=10 so x=3 really helpful if you guys can solve it for me.

• Registered Posts: 72 Regular contributor ⭐
Options
2(2x+2)-3(x-1)=8
4x+4-3x+3=8 (-3*-1=+3)
rearranging, (so that I can see what I've done):
4x-3x+4+3=8
x+7=8
x=8-7
x=1

hope that makes sense
substitute x=1 into equation to confirm:
4+4-3+3=8, which is correct
• Registered Posts: 157 Dedicated contributor 🦉
Options
I got this (4x+2)+(-3x+3)=8 but i don't know why - between brackets changes to + and now you have 4x-3x+2+3=8 so that 1x+5=8 so x=8-5=3 if you put x=3 in equation you have (12+2)-(-9+3)=8 sorry equation was wrong when i put in the first time . it's 2(2x+1)-3(x-1)=8
• Registered Posts: 72 Regular contributor ⭐
Options
The first part of the equation:
2(2x+2)
the 2 outside of the brackets has to be multipied by both parts inside the brackets so:
2*2x + 2*2
ie 4x+4

similarly in the 2nd part, you have to multiply both the x and -1 by -3
-3(x-1)
=-3*x and -3*-1
=-3x + 3

(a minus multiplied by a minus gives a positive answer)
• Registered Posts: 157 Dedicated contributor 🦉
Options
I got it now thank you so much
• Registered Posts: 72 Regular contributor ⭐
Options
No probs
• Registered Posts: 72 Regular contributor ⭐
Options
Are you happy solving the equation, now that you've amended it?
• Registered Posts: 72 Regular contributor ⭐
Options
just checked and yes, x=3 is the correct answer